Dilution Effect on a Mixture Solution of Organic Dyes (Cumarin and Rohdamain) - Wajeha Abdle Diam (Journal of Global Pharma Technology, 2017)
In this study the spectral properties absorption of laser dyes (C480 & R610) mixture have been studied and has been dissolved in ethanol to prepare (1:1,1:21:3,1:4,1:5) ratio from [Rohdamin610(R610): Cumarin 480(C48)]at ( )concentration at room temperature. by added (18,27,36) mel from ethanol per ratio then study the change in the spectral properties of the mixture at each addition. Found that there was a significant increase in the spectral line width by increased the amount of added ethanol and there is red shift increase with Increasing the amount of ethanol added and Decreased in the intensity.Keywords: Dye laser, Dilution. Absorption spectrum.